1999
DOI: 10.1088/0953-8984/11/1/021
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced three-dimensional magnetic ordering in the spin-gap system

Abstract: The temperature and field variations of the magnetization have been measured for which has a singlet ground state with an excitation gap. It is found that undergoes three-dimensional ordering in magnetic fields. The phase boundaries between the paramagnetic and ordered states are determined for and . The phase boundaries for these field directions coincide when normalized by the g-factor. The excitation gap at zero temperature is re-evaluated as .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
263
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(289 citation statements)
references
References 24 publications
26
263
0
Order By: Relevance
“…These double chains are located at the corners and center of the unit cell in the b−c plane, and are separated by Tl + ions. The magnetic ground state is the spin singlet with the excitation gap Δ/k B ≈ 7.5 K. 8,9) The magnetic excitations in TlCuCl 3 were investigated by Oosawa et al, 10) who found that the lowest excitation occurs at Q = (0, 0, 1) and its equivalent reciprocal points, as observed in KCuCl 3 . 11,12) The origin of the gap is the strong antiferromagnetic interaction J = 5.26 meV on the planar dimer Cu 2 Cl 6 in the double chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These double chains are located at the corners and center of the unit cell in the b−c plane, and are separated by Tl + ions. The magnetic ground state is the spin singlet with the excitation gap Δ/k B ≈ 7.5 K. 8,9) The magnetic excitations in TlCuCl 3 were investigated by Oosawa et al, 10) who found that the lowest excitation occurs at Q = (0, 0, 1) and its equivalent reciprocal points, as observed in KCuCl 3 . 11,12) The origin of the gap is the strong antiferromagnetic interaction J = 5.26 meV on the planar dimer Cu 2 Cl 6 in the double chain.…”
mentioning
confidence: 99%
“…9. Since a precise structural analysis for TlCuCl 3 has not been reported, we performed the single-crystal X-ray diffraction.…”
mentioning
confidence: 99%
“…For example, it results in a discontinuous drop in the magnetization at the critical point as we increase the temperature, whereas we only see a dip in experiments. 47 Another apparent disagreement is of the estimate of the exponent φ. Experiments seemed to indicate a larger value for the exponent φ for the QCP than the HF theory does.…”
Section: Scaling and Numerical Resultsmentioning
confidence: 99%
“…In particular, a class of spin-gapped antiferromagnets has provided rich macroscopic quantum phenomena such as spin-Peierls transition and impurity-induced magnetic ordering in CuGeO 3 , 2,3,4,5 and Bose-Einstein condensation of magnons in TlCuCl 3 . 6,7,8 Microscopic aspects of the spin-gapped phase in lowdimensional antiferromagnets have been extensively discussed on the basis of the antiferromagnetic (AFM) Heisenberg model. In general, a spin gap is defined as the energy difference between singlet ground and triplet first-excited states.…”
Section: Introductionmentioning
confidence: 99%